Eliminating Hepatitis B from Bangladesh by the Year 2030 - Mustafa, Md Golam; Alam, Md Shahinul; Azam, Md Golam; Alam, Md Mahabubul; Islam, Md Saiful; Khan, Mobin (Journal of Bangladesh College of Physicians and Surgeons, 2020)
Worldwide, hepatitis B virus (HBV) infection is still a major public health problem. Bangladesh having a large burden of HBV infection, should be a major contributor towards it’s elimination by 2030. The country has been making progress in reducing incidence of HBV infection during the past decades. The progresses are mainly due to large vaccination coverage among children and large coverage of timely birthdose vaccine for prevention of mother-to-child transmission of HBV. However, Bangladesh still faces challenges in achieving target of reduction in mortality from HBV. On the basis of targets of the WHO’s Global health sector strategy on viral hepatitis 2016–2021, we highlight priorities for action towards HBV elimination. To attain the target of reduced mortality we propose that, the service coverage targets of diagnosis and treatment should be prioritized along with vaccination. Firstly, improvements are needed in the diagnostic and treatment abilities of medical institutions and health workers. Secondly, the government needs to reduce the costs of health care. Thirdly, better coordination is needed across existing national program and resources to establish an integrated system for prevention, screening, diagnosis and treatment of HBV infection. In this way, we can make progress towards achieving the target of eliminating HBV from Bangladesh by 2030 J Bangladesh Coll Phys Surg 2020; 38(3): 145-149